The Implementation of Vocal and Music-Based Art Education in Islamic Early Childhood Schools (Raudhatul Athfal) in Medan City - Zannatunnisya; Masganti Sit; Neliwati (Universitas PGRI Yogyakarta, 2025)
This research aims to describe art education in Islamic education at Raudhatul Athfal Ibunda and Bunayya in Medan City. Using a qualitative approach and case study method, data were collected through observation, interviews, and documentation. The results show that vocal and music education is carried out thematically through Islamic songs that are rich in moral values. Raudhatul Athfal Ibunda adopts a systematic and structured approach, with thorough planning, parental involvement, and targeted evaluation. In contrast, Raudhatul Athfal Bunayya is more flexible and emphasizes a play-based learning approach in a joyful environment. The success of art education is not only measured by its musical aspects but also by changes in children’s attitudes that align with Islamic values. These findings contribute to the development of an Islamic values-based art education model in early childhood education. Keywords: art education, islamic education, raudhatul athfal